(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To analyze case of secondary enucleation of a child’s eye with recurrent retinoblastoma (RB) developing due to parents’ failure to take the child to surveillance appointments after salvage eye therapy. Material and Methods: Observation and treatment of a 10-month child diagnosed with bilateral RB. The right eye was diagnosed with RB at stage T1N0M0, and the left eye, with RB at stage T3cN0M0 complicated by secondary glaucoma. Results: Salvage eye therapy was performed which included six cycles of combined multiagent chemotherapy (with systemic intravitreal chemoreduction melphalan injection), followed by three courses of laser coagulation of tumor focus in the right eye and additional seventh local chemotherapy in the left eye. As a result, type 4 RB regression pattern in the right eye, and was developed incomplete type 2 RB regression pattern (“fish-flesh” appearance) in the left eye. However, after the child did not visit the medical care facility for surveillance and treatment during seven months, tumor regrowth developed. Secondary enucleation of the left eye was performed due to big tumor size, anterior chamber involvement blindness, and the absence of visual functions without prospects for their improvement. Histopathology found undifferentiated retinoblastoma with invasion into the episclera, the child was administered two cycles of chemoreduction as well as external beam radiotherapy of the left orbit using a medical linear accelerator system. Conclusion: Should tumor recurrence occur or if there is no tumor control, urgent secondary enucleation with eye ball histopathology and, if indicated, further adjuvant therapy are recommended to prevent metastasis and save child’s life.